Pengaruh Kualitas Produk Dan Varian Produk Terhadap Keputusan Pembelian Pada Toko Alamsyah - Haryani Haryani; Emi Safrina; Muhammad Diah; Deni Firmansyah; Sri Murniyanti (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of product quality and product variants on purchasing decisions at the Alamsyah Store. The sample used in this research was 100 Alamsyah Shop customers. The method in this research is a quantitative method. The research results show that partially or simultaneously product quality and product variants influence purchasing decisions at the Alamsyah Store. Based on the test results of Fcount 54.221 > Ftable 2.70, it can be concluded that product quality variables and product variants simultaneously influence product purchasing decisions at the Alamsyah Bireuen Store.